PENGEMBANGAN MEDIA INFORMASI RUANG KULIAH PADA FAKULTAS TEKNIK UNIVERSITAS PALANGKA RAYA BERBASIS ANDROID DAN LOCATION BASED SERVICE - Licantik Licantik; Nova Noor Kamala Sari (Universitas Palangka Raya, 2019)
Android is a widely used of technology. Location Based Service (LBS) is an android feature to find the location of user’s device by utilizing satellite facilities. Problems faced by the students in Informatics of Faculty of Engineering are the limited number of lecturing rooms and the lack information of the use of those rooms. LBS feature on android will answer those existing problems. The methodology for development is Prototype by Pressman which has saveral stages namely (1) communication and initial data collection, (2) quick design, (3) formation of prototype, (4) evaluation of prototype, (5) improvement of prototype and (6) final production. Flowchart is made at analysis stage as well as Unified Modeling Language (UML) at the design stage. The language programs are Java, JSON, SQLite. Map plans are designed through Google Earth Pro and Edraw Max 7 placed on the Google Map API where data storage is made in the Firebase and SQLite online databases as local databases with application development created by Android Studio. Application of Location Based Service (LBS) in Faculty of Engineering of University of Palangka Raya is applied the Google Map API by each marker point being made which generates various radius. When the application user enters into each radius, it will produce a notification of room information that contains lectures taking place in the rooms. Therefore, the rooms associated with lectures is identified